Quality of management of cooperation of science business-administration in Polish academic cities - Odzimek, Tomasz (Jakość zarządzania współpracą nauki, biznesu i administracji w polskich miastach akademickich, 2019)
The paper describes the problems of a knowledge-based economy and the creation of new knowledge and technology as a result of cooperation between science, business and local administration. These entities, working together, form the so-called triple helix of science, business and administration. The key issue is the process of managing the triple helix by universities and the local administration, and therefore public entities. Therefore the research aim was to determine the quality of management of collaboration of science, business and administration in Polish academic cities by local entities of the public sector. In this area, a survey was conducted in 20 large academic cities of higher education institutions, city councils and local innovation centres that coordinate the triple helix. The respondents were the entities of city halls, universities and innovation centres and were examined using a questionnaire. The final conclusion was preceded by a comprehensive presentation of the quality of management, including all four management functions
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 196-208
Keywords: triple helix; quality of management; potrójna helisa; jakość zarządzania; współpraca nauka-biznes-administracja